Kemampuan Siswa Dalam Memahami Materi Limit Fungsi Aljabar Terintegrasi Dengan Ayat-Ayat Al-Qur’an Menggunakan Model Discovery Learning Kelas XI MAN 2 Halut - Sitna Maryam Saleh; Kurnia Saleh (EDUKASI, 2023)
This study aims to measure students' ability to understand Algebraic Limits of Function material which is integrated into the verses of the Qur'an using the discovery learning model in class XI IPA Madrasah Aliyah Negeri 2 Halmahera Utara for the 2021/2022 Academic Year. The research method is classroom action research (CAR). Data collection techniques used tests in cycle I and tests in cycle II, while data analysis used descriptive analysis to determine individual student learning completeness, classical completeness KKM) Mathematics class XI IPA 1 set at Madrasah Aliyah Negeri 2 Halmahera Utara is 75. The results showed that students of class XI IPA 1 Madrasah Aliyah Negeri 2 North Halmahera had the ability to understand Algebraic Function Limit material which was integrated into the verses of the Qur'an using the discovery learning model and there was an increase in student learning outcomes through the application This discovery learning model can be seen from the learning outcomes in the first cycle which achieved completeness of only 8 students (31%) while in the second cycle it increased to 21 students (81%).